CD1b-restricted GEM T cell responses are modulated byMycobacterium tuberculosismycolic acid meromycolate chains - Andrew Chancellor; Anna S. Tocheva; Chris Cave-Ayland; Liku B. Tezera; Andrew White; Juma’a R. Al Dulayymi; John S. Bridgeman; Ivo Tews; Susan Wilson; Nikolai M. Lissin; Marc Tebruegge; Ben G. Marshall; et al. (2017)
Significance Tuberculosis is a major global pandemic responsible for more deaths than any other infectious disease, yet no effective vaccine exists. Here, we demonstrate CD1b expression within human tuberculous granulomas, supporting a role for CD1b lipid antigen presentation in host immunity to infection. CD1b presents mycolates, the dominant Mycobacterium tuberculosis (Mtb) cell wall lipid class and key virulence factors, to αβ T cells. We reveal that mycolate tail moieties, distal to the head group, are antigenic determinants for the conserved human germline-encoded mycolyl lipid-reactive (GEM) T cell receptors (TCRs). Computational simulations suggest a putative mechanism whereby lipid-ligand dynamics within CD1b regulate GEM-TCR activity. This work provides insights for the development of major histocompatibility complex (MHC)-independent Mtb lipid vaccines, including those that target GEM T cells.